2007
DOI: 10.1111/j.1600-0722.2007.00457.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel nonsense mutation in PAX9 is associated with marked variability in number of missing teeth

Abstract: Tooth development is under strict genetic control. During the last decade, studies in molecular genetics have led to the identification of gene defects causing the congenital absence of permanent teeth. Analyses of PAX9 and MSX1 in nine families with hypodontia and oligodontia revealed one new PAX9 mutation. A LOD score of Z = 1.8 (theta = 0.0) was obtained for D14S75 close to PAX9 in one three-generation family, and sequencing of the gene identified the nonsense mutation c.433C>T. The mutation results in a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 26 publications
1
27
0
1
Order By: Relevance
“…12,14 In humans, dominant mutations in PAX9 have been identified as a cause of congenital absence of some posterior (and occasionally anterior) teeth. Frame-shift, [15][16][17] insertion, 18,19 missense 18 and non-sense 20,21 mutations, as well as whole-gene deletion, 18,22,23 have been described in families exhibiting hypodontia, primarily with absence of molar teeth. In addition, it has been shown that common polymorphisms in PAX9 are associated with 3rd molar (M3) agenesis.…”
Section: Introductionmentioning
confidence: 99%
“…12,14 In humans, dominant mutations in PAX9 have been identified as a cause of congenital absence of some posterior (and occasionally anterior) teeth. Frame-shift, [15][16][17] insertion, 18,19 missense 18 and non-sense 20,21 mutations, as well as whole-gene deletion, 18,22,23 have been described in families exhibiting hypodontia, primarily with absence of molar teeth. In addition, it has been shown that common polymorphisms in PAX9 are associated with 3rd molar (M3) agenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Some mutations associated with tooth agenesis have been identified in humans at the MSX1 (Vastardis et al, 1996;Lidrali et al, 1998;Lidral & Reising, 2002;Mostowska et al, 2006) and PAX9 (Schuffenhauer et al, 1999;Stockton et al, 2000;Nieminen et al, 2001;Das et al, 2002;Pereira et al, 2006;Hansen et al, 2007;Tallon-Walton et al, 2007;Zhao et al, 2007;Guala et al, 2008) genes. Nevertheless, these genes might be fundamentally implicated in the www.intechopen.com Maxillary Lateral Incisor Agenesis (MLIA) 279 odontogenesis of posterior teeth (Pinho et al 2010b).…”
Section: Etiologymentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14] The MSX1 genes with a homeodomain and the PAX9 genes with a paired domain encode transcription factors that are essential for craniofacial and dental development of the mesenchyme. [15][16][17][18][19] Generally, mutations in MSX1 and PAX9…”
Section: Introductionmentioning
confidence: 99%